The anti-osteoporotic effect of puerarin on the femoral bone in rat models of osteoporosis: a systematic review and meta-analysis - Yang, Zhaoxi; Tang, Rui; Ma, Yulin; Luo, Wenlong; Hu, Yimei (Frontiers in Pharmacology, 2026)
ObjectiveIn this systematic review and meta-analysis, we aimed to evaluate the anti-osteoporotic efficacy of puerarin in rodent models of osteoporosis (OP) and to explore the impact of the dosage, treatment duration, and intervention method.MethodsA comprehensive search of electronic databases (e.g., PubMed, Embase, Web of Science, CNKI, and Wanfang) was conducted through August 2025. Randomized controlled trials investigating the effects of puerarin monotherapy on osteoporotic rats were included. The primary outcome measured was bone mineral density (BMD), and the secondary outcomes included bone histomorphometric parameters (BV/TV, Tb.Th, Tb.N, and Tb.Sp) and bone turnover markers (e.g., PINP, BALP, CTX, TRACP, and osteocalcin). Data were pooled using a random-effects model, and subgroup analyses were performed based on the puerarin dose, treatment duration, and intervention method. The study quality was assessed using the SYRCLE risk-of-bias tool.ResultsTwenty-eight studies involving 570 animals were included. The meta-analysis demonstrated that puerarin significantly increased femoral BMD (SMD = 2.95, 95% CI: 2.32 to 3.58, and p < 0.00001) and improved the bone microarchitecture by increasing BV/TV, Tb.Th, and Tb.N, and decreasing Tb.Sp. Subgroup analysis revealed that the most pronounced BMD improvement occurred at doses ≥50 mg/kg/day administered for ≥8 weeks. Puerarin significantly suppressed bone resorption markers, CTX and TRACP, and elevated serum levels of osteocalcin, calcium, and phosphorus. However, its effects on bone formation markers, PINP and BALP, were not statistically significant.ConclusionPuerarin exhibits significant therapeutic potential for OP in rat models by increasing BMD, improving bone quality, and rebalancing bone metabolism in favor of formation, primarily through the inhibition of resorption. The optimal effect appears to be dose- and duration-dependent. Although these preclinical findings are promising, the clinical translation of puerarin requires validation through larger-scale, high-quality animal studies and subsequent clinical trials.